Bridging the Literacy Gap: Read-Aloud Implementation in a University-Based Daycare Center - Azizatur Rahma; Annisa Fitranova Khaylila Marcianno; Arief Darmawan; Muhammad Nur Hanif (Universitas Trunodjoyo Madura, 2026)
Previous studies have shown that Indonesia's literacy rate remains low, primarily due to a lack of reading interest. Experts in linguistics and early childhood education attribute this to the absence of pre-reading activities such as read-aloud sessions, despite recommendations from the Indonesian Ministry of Education and Culture. Research on the implementation of read-aloud activities in non-formal educational institutions is still limited, even though many young children spend their early years in daycare due to their parents' work commitments. One such case is the Dharma Wanita Persatuan Daycare at UIN Walisongo Semarang, which, despite being under a state Islamic higher education institution, had not implemented read-aloud activities. Over a two-month period, the researchers optimized read-aloud sessions at the daycare. The results read-aloud activities can increase children’s reading interest, as evidenced by the fulfillment of five out of six indicators of reading enjoyment. Those indicators are: (1) the need for reading materials; (2) the initiative to seek out reading materials; (3) enjoyment of reading; (4) the desire to read continuously; and (5) interest in reading materials. To sustain and further improve this interest, daily read-aloud activities should be consistently carried out by caregivers following the optimization period.